Technological Progress and Economic Geography_x0003_ - Jacques Thisse; Takatoshi Tabuchi; Xiwei Zhu (European Regional Science Association (ERSA), 2014)
New economic geography focuses on the impact of falling transport costs on the spatial distribution of activities. However, it disregards the role of technological innovations, which are central to modern economic growth, as well as the role of migration costs, which are a strong impediment to moving. We show that this neglect is unwarranted. Regardless of the level of transport costs, rising labor productivity fosters the agglomeration of activities, whereas falling transport costs do not affect the location of activities. When labor is heterogeneous, the number of workers residing in the more productive region increases by decreasing order of productive efficiency when labor productivity rises.
Keywords: J61; R12; 330; new economic geography; technological progress; labor productivity; migration costs; labor heterogeneity